A multifunctional graphene-based nanofiltration membrane under photo-assistance for enhanced water treatment based on layer-by-layer sieving - Zhang, Qi; Chen, Shuo; Fan, Xinfei; Zhang, Haiguang; Yu, Hongtao; Quan, Xie (Applied catalysis. B, Environmental, 2018)
[Display omitted] •Photocatalysis was introduced to NF membrane separation and obtained much improved water flux.•Membrane showed efficient rejection of Na2SO4 and removal of ammonia, antibiotic and bisphenol A.•The membrane exhibited high performance on real aquaculture wastewater treatment.•Lost flux of fouled membrane could be recovered under photochemical assistance. Nanofiltration (NF) provides an effective strategy for rejecting large organic molecules. However, attaining high permeability, antifouling ability and good selectivity simultaneously still remains a crucial task for existing NF technologies. Herein, we built a photo-assisted multifunctional NF membrane assembled with g-C3N4, TiO2, carbon nanotubes (CNTs) and graphene oxide (GO), in which CNTs not only expand the interlayer space between neighbored graphene sheets, but also enhance the stability and strength of GO layer. Benefiting from the photo-assistance, our NF membranes show an enhanced water flux (∼16Lm−2h−1bar−1), while keep a high dye rejection (∼100% for Methyl Orange). The photo-assisted NF membranes also display good rejection ratio for salt ions (i.e., 67% for Na2SO4) due to the layer-by-layer sieving. Meanwhile, the NF membrane coupled with photocatalysis exhibits a multifunctional characteristic for the efficient removal of ammonia (50%), antibiotic (80%) and bisphenol A (82%) in water. Besides, the performance of integrated system is also tested by treating the real aquaculture wastewater to evaluate its practical application ability. The lost flux of the fouled membrane is effectively recovered by the photochemically assisted process. Hence, this work mitigates the longstanding challenge of GO-based NF membranes in large-scale application by integrating photocatalysis and nanofiltration technologies.